Analysis of Seasonal Price Fluctuations of Paddy (Boro) in Bangladesh (SAARC Journal of Agriculture, 2021)
This paper has focused on seasonal variations of price and trend of the price escalation of paddy in Bangladesh using monthly average wholesale price of Boro paddy over a period from 2001 to 2019. Secondary data were used in this study and collected from different secondary sources. The multiplicative model was exercised in this study; the least square method was applied to find out the long-term changes occurring in the price of paddy and the ratio to moving average method was used to measure seasonal fluctuations in price of paddy. It was evidently observed from the study that seasonal fluctuations in price of paddy prevail in Bangladesh as seasonal indices were deviated from hundred in different months. April to August, the price of paddy was lower compare to other months’ price because April and Mayare the harvesting period of Boro paddy and resulted in more supply to the market. From August, it was increasing gradually and reached to the highest position on March with 112.15. Long-term trend analysis showed that prices of paddy will increase Tk. 72.80 per quintal higher annually compare to the country’s average price.SAARC J. Agri., 18(2): 219-226 (2020)